Designing and Validating the Proposed Parent Involvement Model for Elementary Students - Habibi, Samira; Aliabadi, Khadijeh; Ahmadabadi, Mohammadreza Nili; Zavaraki, Esmaeil Zareii (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to design and validate the parental involvement model for elementary school students. The research method was used for model design stage, descriptive-analytical method with inductive content analysis approach and for descriptive model validation, descriptive survey method was used. The statistical population for the design of the proposed model consisted of extracted transcripts from interviews with 27 expert teachers, teachers and parents and all upstream documents, books, and articles (from 2000 to 2018) from subject databases, It was downloadable that, through sampling, in addition to the text of the interviews, 70 documents were selected for content analysis and then theoretical saturation was obtained. The statistical community was formed to validate the model including all teachers and faculty members and experts of the Organization of Education, Parents and Teachers. 26 were selected through purposeful sampling for interview. Data were collected through semi- structured interviews, fingerprints, and a 7-item Likert-scale questionnaire whose content validity was 0.89 using Cronbach’s alpha. Data were analyzed using qualitative content analysis and Max Keyword software. Based on the inductive content analysis and continuous comparison of the obtained codes, five main components of analysis, decision making, family interaction and education, dimensions of family participation and evaluation and feedback, and 55 sub-components were extracted for the main components. After analyzing the content and extracting the codes, the components and sub-components were presented in a template format. First, the conceptual model that incorporated all of these elements was designed and then a process model that was applicable and applicable was designed. At the level of descriptive statistics, mean and standard deviation, and at the level of inferential statistics, one-sample t-test was used to answer the internal validity of the model. Validation findings from the experts’ point of view showed that the characteristics of the proposed parental participation model elements for elementary school students were well-qualified and had a score above 3. Therefore, this model was evaluated by appropriate and practical experts. Therefore, it is suggested that this model be introduced as one of the executive strategies for one of the major goals in the document of fundamental transformation of education "increase of participation and public effectiveness especially of family in education excellence."